2018
DOI: 10.21873/anticanres.13106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New-generation Fecal Immunochemical Test (FIT) With Guaiac Fecal Occult Blood Test (gFOBT) in Detecting Colorectal Neoplasia Among Colonoscopy-referral Patients

Abstract: Background/Aim: The aim of the present study was to compare fecal immunochemical tests (FITs) for colorectal cancer (CRC) screening with the traditional guaiac-based FOB tests (gFOBT). Materials and Methods: A cohort of 368 colonoscopy-referral patients were evaluated by i) the new-generation FIT: ColonView quick test (CV; Biohit Oyj, Finland) and ii) a conventional gFOBT HemoccultSENSA (HS; Beckman Coulter, USA). Three fecal samples were requested for both assays, and all subjects underwent diagnostic colonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 23 publications
(43 reference statements)
7
49
0
Order By: Relevance
“…For the adenoma endpoint, the difference in sensitivity between ColonView test and gFOBT was even larger (sensitivity of 44% versus 19%, respectively). The authors concluded that due to its 95% sensitivity, ColonView test is superior to gFOBT in organized CRC screening (27).…”
Section: Fitsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the adenoma endpoint, the difference in sensitivity between ColonView test and gFOBT was even larger (sensitivity of 44% versus 19%, respectively). The authors concluded that due to its 95% sensitivity, ColonView test is superior to gFOBT in organized CRC screening (27).…”
Section: Fitsmentioning
confidence: 99%
“…The FIT is based on the detection of the globin moiety of human hemoglobin or its degradation products. In a recent systematic review of FITs in CRC screening (21,27), 12 types of FITs were identified in the literature, representing 20 different proprietary names. Due to the major differences in test methodology, the authors were unable to assess all FITs as a class, however, and undertook a sub-group analysis (15,21).…”
Section: Fitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study Population. This retrospective study analyzed a total of 90 formalin-xed para n-embedded (FFPE) samples removed from 87 patients during diagnostic colonoscopy from 2014 to 2016 at Barretos Cancer Hospital 57 . Samples included 67 adenomas (39 early and 28 advanced adenomas), 7 sessile serrated lesions and 16 hyperplastic polyps.…”
Section: Methodsmentioning
confidence: 99%